Exploring the Determinant Factors of Impulsive Buying Behavior during the COVID-19 Pandemic among Indonesian Consumers - Rahmawati, Rahmawati; Primanto, Alfian Budi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2021)
The COVID-19 pandemic has ravaged the global economy, igniting much fear and panic that disrupted buying patterns and behavior. This study aims to investigate the phenomenon of impulsive buying behavior during the COVID-19 crises by exploring the influences of panic buying, perceived scarcity, and the mediation role of fear appeals. This study uses path analysis which is processed by using the Preacher-Hayes technique. A total of 243 respondents participated in the study. The result of this study revealed that perceived scarcity and panic buying were successfully proved to be significant predictors of impulsive buying behavior. However, the direct effect of fear appeals and the mediation role of fear appeals and panic buying on the relationship between perceived scarcity and impulsive buying behavior were failed to prove in this study.